الابتكار أداة لجذب المستهلكين ومواجهة المنافسة في مؤسسات الاتصال الجزائرية بالإشارة إلى مؤسسة موبيليس- دراسة تحليلية - - بارك, نعيمة (Université de M'sila, 2011)
مع بداية القرن الواحد و العشرين و في ظل التطورات التي شهدها العالم المعاصر، و ما تفرضه من التغيرات المتلاحقة في شتى الميادين المعرفة أصبح الابتكار ضرورة حتمية للمؤسسات الاقتصادية لتطوير مخرجاتها وأساليب عملها بصفة مستمرة وذلك لجذب أكبر قدر ممكن من المستهلكين وتحسين نتائجها وتحقيق التميز ومواجهة المنافسة. فمؤسسات الاتصال بالجزائر أصبحت مضطرة على القيام بتنظيمات جديدة وإدخال هياكل مرنة وكفاءات تمكنها من التلاؤم بسرعة وبسهولة مع ديناميكية المحيط التقني والاجتماعي المحلي والدولي. وتهدف مؤسسة موبيليس من خلال عملية الابتكار إلى تطوير وتجديد عروضها وخدماتها، من أجل جذب أكبر قدر من المشتركين الجزائريين وتحقيق التميز التنافسي.
With the beginning of the twenty-first century and in light of developments in the contemporary world. And what of the changes imposed by successive in various fields of knowledge innovation has become an absolute necessity for economic institutions to develop outcomes and methods of work constantly in order to attract the largest possible amount of consumers and improve their results and achieve excellence and meet the competition . Institutions of Contact in Algeria has become obliged to do with organizations and the introduction of new flexible structures and competencies to enable them to quickly and easily coping with the dynamics of the Pacific technical and social domestic and international . Mobilis Foundation aims through a process of innovation to develop and renew their products and services, in order to attract the largest amount of participants Algerians and achieve competitive excellence
Keywords: الابتكار، مؤسسات الاتصال، المستهلكين، مؤسسة موبيليس